A Togolese woman sells Togolese food at Missebo market, Benin Republic - Lawanson, Taibat; Eleshin, Abisoye (Mobilities and Flows Across West African Urban Corridors, 2022)
A Togolese woman sells Togolese food at Missebo market, Benin Republic
Keywords: West Africa; African Studies; Immigration Studies; Immigration; Knowledge